Strategy of Carpatian region’s economic potential efficiency improvement - Машіка, Г. В. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
This article analyses the ways to increase the economic household usage efficiency strategies in the Carpathian region. The efficiency of strategic administration usage of economic potential in the Carpathian region is stipulated by the provision of human harmonious development, its personal level and welfare, creation of the corresponding conditions to achieve ecologically safe, socially oriented economic development. The author gives her own definition of the strategic administration of economic potential development as a set of measures, tools and factors of influence on the regional development in accordance with the strategy achieved by the common efforts of authorities, business and public institutions. As a result, we achieve the sustainable development of the regions and states in general, and a competitive position in the global market. It has been established to improve the strategic efficiency of the Carpathian region’s economic potential regional authorities must have a certain set of information. The author points out that the regions of Ukraine, including the Carpathian one, have formed fragmented scientific and practical strategic forecasting and administration in various areas of economic activity which has both positive and negative aspects. The positive is the possibility to implement the best world leading practices for our country, and the negative is the lack of a common vision and predictive management activities in this area regulated by various acts, and fragmentation in teaching and methodological procedures for development of plans, forecasts and strategies at the national and local levels. The author notes that the strategic management of the region’s economic potential development needs to assess the potential including the status, efficiency and formation based on the application of a SWOT-analysis, which includes the analysis of strengths, weaknesses, and opportunities and threats. Next, the opportunities to improve the potential are analysed, as well as formation of the optimal structure based on the potential synergistic interaction of its structural components in accordance with the strategic goals.The development strategy of the potential is based on the selected alternative development of the region, monitoring and evaluation of its  implementation to achieve the objectives.